Aiken index-based content validity analysis of argumentation skills and sustainability literacy instruments in STEM-based green chemistry learning - Ardhany, Amellia; Shidiq, Ari Syahidul; Yamtinah, Sri; Masykuri, Mohammad; Saputro, Agung Nugroho Catur (Indonesian Journal of Science and Mathematics Education, 2026)
This study aims to analyze the content validity of instruments measuring argumentation skills and sustainability literacy in STEM learning on green chemistry materials using the Aiken index. This study uses a quan titative design with validation carried out through focused group discussions (FGD) involving eight experts, including five chemistry education lecturers, as well as three high school chemistry teachers, to evaluate the quality of the developed instruments. The instruments included pretest and posttest questions (multiple-choice and essay), questionnaires, observation sheets, product assessment sheets, teaching modules, and student worksheets. Eight expert validators assessed the content, language, and presentation aspects using a Likert scale. The results of the expert assessments were analyzed using the Aiken index to determine the content validity of each item. The findings showed that all instruments achieved Aiken index values of ≥ 0.75, indicating high content validity. These results suggest that the developed instruments are valid and feasible for use in STEM-based green chemistry learning. The implications of this study highlight that the validated instruments can effectively support the measurement of students’ conceptual understanding, argumentation skills, and sustainability literacy, thereby strengthening the integration of STEM approaches in chemistry education.